Esophageal hypercontractility is abolished by cholinergic blockade. Issue 8 (13th November 2020) - Babaei, Arash; Shad, Sadaf; Massey, Benson T.
Abstract: Background: Esophageal hypercontractility (EHC) is considered a major esophageal motor disorder of unclear etiology. Different mechanisms have been proposed, including an imbalance in inhibitory and excitatory esophageal innervation. We hypothesized that patients with EHC suffer from cholinergic hyperactivity. Aim: To interrogate the excitatory and inhibitory neurotransmission in EHC by assessing the esophageal motor response to atropine (ATR) and cholecystokinin (CCK), respectively, in EHC patients. Method: We retrospectively reviewed patients who underwent high‐resolution manometry (HRM) with pharmacologic challenge in a tertiary referral center between 2007 and 2017. We identified 49 EHC patients who were categorized based on frequency of hypercontractile peristaltic sequence into "frequent" and "infrequent" and motility diagnosis groups. Deglutitive pressure metrics and esophageal motor responses to ATR (12 mcg/kg iv) and CCK (40 ng/kg iv) were analyzed across groups. Results: Atropine abolished hypercontractility across all groups studied, converting nearly half of patients to a motor pattern of ineffective esophageal motility. Abnormal CCK responses primarily occurred in the patient groups with concomitant outflow obstruction. Conclusions: Hypercontractility is cholinergically mediated in all esophageal motor disorders. Most patients with isolated EHC appear to have excessive cholinergic drive, rather than loss of inhibitory innervation, and might be candidates for treatment with anticholinergic agents. Abstract : Atropine inhibited esophageal hypercontractility in all patients independent from the amplitude of hypertensive esophageal contractions. Anticholinergic therapy may offer a safe and cost‐effective management option for patients with challenging esophageal hypercontractility disorders.